An evaluation of e-learning of entrepreneurship course: Learning alternative during Covid-19 pandemic for university students - Ernawati, Ernawati; Dewi, Muharika; Rosalina, Linda; Ferdian, Feri; Andres, Fran Serano (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
This research was conducted to present recommendations on the implementation of e-learning courses Entrepreneurship during the Covid-19 pandemic. The evaluation refers to model Kirkpatrick's with Level 1: Satisfaction, Level 2: Learning, Level 3: Behavior, and Level 4: Impact. The research used a quantitative method with data analysis using percentage techniques. The sample was 307 students who had attended Entrepreneurship courses using e-learning. Data were collected using a questionnaire distributed via Google form. The results show that the evaluation level 1: student satisfaction in learning, on average of 67% and 33% of the other feeling dissatisfied and less able to accept entrepreneurship learning optimally. Level 2 evaluation: learning outcomes, data cognitive, affective, and psychomotor have an average improvement. Evaluation level 3: there was an average improvement of only 18 points on entrepreneurial behavior. Evaluation level 4: 53% of students respond that e-learning is suitable for sustainable use, 59% give the opinion that e-learning is effective in increasing the ability to be an entrepreneurial, and 52% undertake entrepreneurial activities after participating in e-learning. The recommendation of this study's results is to continue learning by using e-learning by paying attention to process factors and combining it with learning, which refers more to implementing entrepreneurial projects to improve psychomotor competence and entrepreneurial behavior in the future.